Immunosuppressive Agents and Thoracic Aortic Aneurysm: Real Correlation or Mere Coincidence? - Ostovar, Roya; Laux, Magdalena; Kuehnel, Ralf-Uwe; Schroeter, Filip; Braun, Christian; Erb, Michael; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2021)
Background Atherosclerosis, hypertension, age, and fibrillopathies are well-known risk factors for the development of aortic aneurysm. We discovered that a significant proportion of our patients were previously on chemotherapy treatment or long-term treatment with cytostatic agents or immunosuppressive drugs. Thus, we examined this phenomenon.Methods A total of 224 patients with thoracic aorta aneurysm were retrospectively analyzed after aortic surgery from 2006 to 2016. Seventy-three patients received aortic wrapping and 151 patients underwent aortic replacement of which 89 had a valve-carrying conduit and 62 a supracoronary ascending replacement. Aortic morphology was assessed by means of compute tomography scan before and after surgery. Demographic data, risk profile, and postoperative complications were collected. Short- and long-term survival analysis was performed. Statistical analysis was performed with SPSS 19.0.Results Eighty-eight of 224 patients undergoing aortic surgery because of aortic aneurysm had previously or currently been treated with immunosuppressive agents. Dilatation of the ascending aorta was more pronounced in patients without such therapy. Demographic profile, intraoperative, as well as short- and long-term postoperative results did not differ significantly between both groups.Conclusion The potential effect of immunosuppressant and cytostatic therapies on the development of an aortic aneurysm needs further study. Because of the astoundingly high proportion of these patients being found in an unselected aortic aneurysm cohort with immunosuppressive therapy in the past should be monitored for potential development of aortic aneurysm. If it occurs and requires treatment these patients can fortunately be operated upon with the same short- and long-term outcome than patients without such previous therapy.
Keywords: aortic aneurysm; immunosuppressant; aortic surgery; aortic wall; risk factor